2014
DOI: 10.1200/jco.2013.52.8331
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Screening With Annual Magnetic Resonance Imaging and Mammography: Results of the Initial Screen From the Ontario High Risk Breast Screening Program

Abstract: Screening with annual MRI combined with mammography has the potential to be effectively implemented into an organized breast screening program for women at high risk for breast cancer. This could be considered an important management option for known BRCA gene mutation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 36 publications
4
81
1
Order By: Relevance
“…However, in the presence of a cancer predisposition syndrome, germline mutation in a known cancer predisposition gene, significant family history, or prior personal history of ionizing radiation to the chest, consideration may be given to screening breast MRI. 36,37 Of note, some members of the panel considered that women harboring p53 mutations should minimize exposure to ionizing radiation and thus avoid mammography, and be screened by ultrasound and MRI (level of evidence: Expert Opinion) 38 . The recommended staging, including axillary assessment, does not differ from that for older breast cancer patients.…”
Section: General Considerations When Caring For Young Women With Breamentioning
confidence: 99%
“…However, in the presence of a cancer predisposition syndrome, germline mutation in a known cancer predisposition gene, significant family history, or prior personal history of ionizing radiation to the chest, consideration may be given to screening breast MRI. 36,37 Of note, some members of the panel considered that women harboring p53 mutations should minimize exposure to ionizing radiation and thus avoid mammography, and be screened by ultrasound and MRI (level of evidence: Expert Opinion) 38 . The recommended staging, including axillary assessment, does not differ from that for older breast cancer patients.…”
Section: General Considerations When Caring For Young Women With Breamentioning
confidence: 99%
“…In addition, mri recall rates in their study declined dramatically from 26% on initial screening to 13% on second screening and 10% on third screening, emphasizing an improvement with successive rounds of screening. That finding was reinforced by Chiarelli and colleagues 9 in their report of the Ontario Breast Screening Program evaluating mri and mammography in high-risk women. Those authors observed lower recall rates with subsequent rounds of screening (when images from a baseline mri are available for comparison) and with increased experience of mri use at testing centres.…”
mentioning
confidence: 88%
“…Notably, in relevant studies, despite the higher detection rate, a benefit in survival with the adoption MRM has not been apparent [18,19]. The risks of frequent screening, especially with MRM, include false-positive diagnoses, leading to unnecessary biopsies and/or surgeries, adding in financial and psychological costs, although there is evidence supporting a sharp reduction of false-positives after the first three to five MRMs [20,21]. Concerns have also been voiced on the impact of radiation administered during mammograms.…”
Section: Clinical Implications For Mutation Carriers Surveillance Strmentioning
confidence: 99%